Diagnostic Criteria for Macular Edema Associated with Venous Occlusions - A. G. Shchuko; V. V. Bukina; A. V. Borisova; T. N. Iureva (Acta Biomedica Scientifica, 2020)
Background. Macular edema is considered as a risk factor for a significant decrease in the visual acuity and quality of life of the patient, regardless of its cause. The search for the causes of macular edema in some cases should include an interdisciplinary approach and laboratory studies to correctly determine its etiology and management tactics for such patients. Therefore, the differentiation of the etiology and pathogenesis of macular edema at the stage of diagnosis determines the possibility of preserving not only visual functions, but in some cases the patient's life.Aim: to present clinical cases of macular edema associated with central retinal vein thrombosis of various etiologies. Materials and methods. A prospective study of individual patients with macular edema associated with thrombosis of central retinal vein or its branches was conducted in real clinical practice. All patients underwent a standard ophthalmological examination, as well as optical coherence tomography, and a patient with suspected macroglobulinemia underwent a biochemical blood test.Results. In the first clinical case, macular edema was associated with an exudative form of retinal arterial macroaneurysm. The patient underwent direct laser coagulation of retinal arterial macroaneurysm. 6 months after direct laser coagulation of macroaneurysm, the best corrected visual acuity of the left eye was 1.0. The fundus - macroaneurysm, retinal edema, solid exudates are not ophthalmoscopic. In the second clinical case, macular edema, thrombosis of central retinal vein is associated with Waldenstrom disease. Follow-up and treatment of the underlying disease by a hematologist were recommended.Conclusion. Thus, macular edema proceeding against the background of central retinal vein thrombosis and its branches, having atypical symptoms in the form of ring-shaped deposition of hard exudates, exudative retinal detachment, the presence of a bilateral process, as well as resistance to anti-VEGF therapy require a careful collection of the patient's medical history and the presence of other ophthalmic vascular pathology.